Beyond Technology: Integrated Digital Leadership and Quality Assurance in Islamic Educational Institutions - Riyanto, Riyanto (JURNAL AL-TANZIM, 2026)
Digital transformation demands that Islamic educational institutions improve the quality of education without neglecting Islamic values. This study aims to analyse integrative digital leadership in digital governance to improve the quality of education in Islamic educational institutions. This study uses a qualitative case study design with institutional leaders, academic managers, teachers, administrative staff, and digital system managers. Data were collected through in-depth interviews, non-participant observation, and document analysis, and were then analysed thematically. The results of the study indicate that integrative digital leadership aligns technological innovation with Islamic vision and values; value-based management integrates technology with spirituality in institutional practices; and comprehensive governance supports sustainable institutional performance through digital systems and quality assurance. The study implies that strengthening integrative digital leadership, developing value-based management, and implementing systematic digital governance are strategic needs. Islamic educational institutions need to integrate technology with spiritual values to improve quality, sustain institutional performance, and enhance the effectiveness of quality assurance in the digital era.